Dry ice blasting dual-silane compounded modified wood flour polyurethane composite material and preparation method thereof
Patent Information
- Application Number
- CN202611447510.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-09-17
- Publication Date
- 2026-11-03
AI Technical Summary
现有技术中松散木屑在干冰爆破中爆燃效率低下且储存稳定性差,存在氧气接触不充分、易吸潮结块、散落及粉尘爆炸风险的问题。
The wood chips modified by bissilane compound are uniformly embedded in the polyurethane foam matrix to form a porous structure, providing three-dimensional permeation channels and moisture protection, ensuring complete reaction and stability of the wood chips.
It improves the combustion rate and energy release efficiency of wood chips, maintains the stability of the material in low-temperature environments, reduces the risk of dust explosions, and enhances the convenience of transportation and storage.
Smart Images

Figure CN123026901A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of explosive materials technology, specifically relating to a dual-silane compound modified wood chip polyurethane composite material for dry ice blasting and its preparation method. Background Technology
[0002] Dry ice blasting is a physical process that uses high-speed jets of dry ice particles to impact the surface of an object, leveraging the kinetic energy, thermal shock, and gas expansion effect generated by the sublimation of dry ice to achieve cleaning, peeling, or fragmentation. To improve the energy release efficiency of dry ice blasting, existing technologies attempt to introduce combustible materials into the blasting process. Wood chips, as a widely available and inexpensive biomass fuel, release a large amount of heat and gaseous products through their combustion reaction, potentially synergistically enhancing the blasting effect with the physical expansion effect of dry ice.
[0003] In existing technologies, the application of loosely piled sawdust as a blasting material presents challenges. Because the sawdust is concentrated in a confined space, oxygen can only permeate through gaps. Ensuring the reliability of the blasting material requires maintaining open gaps, which conventional stacking methods cannot achieve. This results in many particles within the sawdust failing to react completely due to insufficient oxygen contact. Therefore, directly using piled sawdust as a blasting material leads to technical difficulties such as surface smothering, slow deflagration, unconcentrated energy release, and unstable blasting effects. Furthermore, sawdust is highly hygroscopic, easily absorbing moisture and clumping in humid environments, significantly reducing its deflagration performance. During transportation and storage, loose sawdust is prone to scattering and dust generation, causing material loss and posing a dust explosion hazard. For dry ice blasting operations requiring underground or field use, the long-term storage stability and ease of transportation of the material are crucial.
[0004] In summary, existing technologies lack a solution that can simultaneously address the two major problems of low combustion efficiency and poor storage stability of loose sawdust. Therefore, current technologies in the field of dry ice blasting face the challenge of simultaneously ensuring rapid and complete combustion of sawdust and maintaining stability during transportation and storage. Summary of the Invention
[0005] The purpose of this invention is to provide a dual-silane compound modified wood chip polyurethane composite material for dry ice blasting, in order to solve the technical problem in the field of dry ice blasting that it is difficult to simultaneously ensure rapid and complete combustion of wood chips and the stability of transportation and storage.
[0006] The aforementioned bissilane-modified wood chip polyurethane composite material for dry ice blasting includes a polyurethane foam matrix and bissilane-modified wood chips, wherein the bissilane-modified wood chips are uniformly dispersed and embedded in the polyurethane foam matrix, and the bissilane-modified wood chips are obtained by modifying wood chips with bissilane.
[0007] Preferably, the amount of bissilane-modified wood chips added is 70-90% of the mass of the polyurethane foam matrix.
[0008] Preferably, the bissilane compound modification is carried out using a bissilane compound hydrolysate, which includes aminosilane and epoxysilane.
[0009] Preferably, the raw materials of the polyurethane foam matrix include component A and component B, wherein component A is a mixture of polyether polyol, amine catalyst and foaming agent, and component B includes isocyanate; the mass ratio of component A to component B is 1.0 to 1.1.
[0010] Preferably, the particle size of the bissilane-modified wood chips is 0.1~3mm, and the moisture content of the bissilane-modified wood chips is not greater than 0.5%.
[0011] The present invention also provides a method for preparing the bissilane-modified wood chip polyurethane composite material for dry ice blasting as described above, comprising the following steps: S1. Screen and dry the sawdust to obtain pretreated sawdust; S2. Prepare a bissilane compound hydrolysate by dissolving aminosilane and epoxysilane in a solvent, adjusting the solvent to acidity, and then stirring to hydrolyze until the solution is clear and transparent. S3. Pretreated wood chips were spray-modified with a bissilane compound hydrolysate, and then aged and dried to obtain bissilane compound modified wood chips. S4. Mix polyether polyol, amine catalyst and foaming agent evenly to form component A, add bissilane compound modified wood chips and stir to premix, to obtain a uniformly dispersed bissilane compound modified wood chips mixture system. S5. Add isocyanate to the mixture and stir. Pour into a mold for free foaming and solidify to obtain the finished product.
[0012] Preferably, in step S2, the aminosilane is KH550, the epoxysilane is KH560, the solvent is a mixture of deionized water and anhydrous ethanol, the total silane mass fraction of the bissilane compound hydrolysate is 1.5%~3%, the hydrolysis pH is 4.5~5.0, and the stirring hydrolysis time is 30~60 min.
[0013] Preferably, in step S3, the amount of the bissilane compound hydrolysate used is 6% to 10% of the wood chips mass.
[0014] Preferably, in step S4, the stirring method is ultrasonic-assisted mechanical stirring; the mechanical stirring speed is 150~200 rpm, the ultrasonic frequency of ultrasonic assistance is 20~40 kHz, and the premixing time is 6~10 min.
[0015] Preferably, in step S5, the isocyanate index is 1.05~1.10, and the stirring time is 10~15s. This invention has the following advantages: It uses polyurethane foam to form a porous framework, with a high proportion of sawdust uniformly embedded in the open and semi-open structure of the polyurethane foam. The interconnected pores of the foam provide three-dimensional permeation channels for oxygen, fully exposing the effective specific surface area of the sawdust; ensuring that the sawdust reacts quickly and completely during dry ice blasting, allowing the blasting energy to be released instantly and maximizing efficiency. Simultaneously, the polyurethane foam matrix provides multiple layers of protection for the internal sawdust, including moisture resistance, oxidation prevention, and protection against mechanical breakage, effectively solving the technical problems of loose sawdust easily absorbing moisture, clumping, and scattering, significantly improving performance stability and meeting the stability requirements of dry ice blasting. Attached Figure Description
[0016] Figure 1 , Figure 2 This is a photograph of a bissilane-modified wood chip polyurethane composite material for dry ice blasting according to the present invention. Detailed Implementation
[0017] The following detailed description of the embodiments, with reference to the accompanying drawings, will further illustrate the specific implementation of the present invention, in order to help those skilled in the art to have a more complete, accurate, and in-depth understanding of the inventive concept and technical solution of the present invention.
[0018] like Figures 1-2 As shown, the present invention provides a bissilane-modified wood chip polyurethane composite material for dry ice blasting, comprising a polyurethane foam matrix and bissilane-modified wood chips, wherein the bissilane-modified wood chips are uniformly dispersed and embedded in the polyurethane foam matrix, and the bissilane-modified wood chips are obtained by modifying wood chips with bissilane.
[0019] In this invention, wood chips are uniformly embedded in the open and semi-open structure of polyurethane foam. The interconnected pores of the foam provide three-dimensional permeation channels for oxygen, fully exposing the effective specific surface area of the wood chips. Explosive combustion occurs through the polyurethane foam matrix, creating a three-dimensional homogeneous combustion phenomenon. The explosion rate of this solution is increased by more than 50% compared to directly using wood chips as fillers. Simultaneously, the wood chips are embedded within the polyurethane foam matrix, thus receiving protection from the matrix. This effectively solves the technical problems of loose wood chips easily absorbing moisture, clumping, and scattering. After three months of storage at room temperature, the moisture content changes by no more than 1%, and the explosion rate decreases by no more than 8%, significantly improving performance stability.
[0020] The bissilane compound modification is carried out using a bissilane compound hydrolysate, which includes aminosilane and epoxysilane.
[0021] The particle size of the bissilane-modified wood chips is 0.1~3mm, and the moisture content of the bissilane-modified wood chips is no more than 0.5%.
[0022] The amount of bissilane-modified wood chips added is 70-90% of the mass of the polyurethane foam matrix.
[0023] The raw materials of the polyurethane foam matrix include component A and component B. Component A is a mixture of polyether polyol, amine catalyst and foaming agent, and component B includes isocyanate.
[0024] The mass ratio of component A to component B is 1.0 to 1.1.
[0025] The polyurethane foam matrix of this invention exhibits excellent low-temperature environmental adaptability, maintaining structural integrity even in the low-temperature environment of dry ice explosion (-78.5℃), without brittleness or detachment. Compared to loose sawdust, which is easily affected by water vapor condensation and its performance deteriorates at low temperatures, the material of this invention is not affected by the low-temperature environment, and its deflagration rate and reaction efficiency do not show significant attenuation, ensuring stable performance of dry ice explosion under low-temperature conditions.
[0026] This invention also provides a method for preparing a bissilane-modified wood chip polyurethane composite material for dry ice blasting, comprising the following steps: S1. Screen and dry the wood chips to obtain pretreated wood chips.
[0027] In this step, the moisture content of the sawdust after drying is controlled to be no more than 0.5%.
[0028] S2. Prepare a bissilane compound hydrolysate by dissolving aminosilane and epoxysilane in a solvent, adjusting the solution to acidity, and then stirring to hydrolyze until the solution is clear and transparent.
[0029] In this step, glacial acetic acid is added to adjust the solution to achieve the hydrolysis pH. The resulting solution after hydrolysis is a bissilane compound hydrolysate.
[0030] The mass ratio of aminosilane to epoxysilane is 1.0 to 1.05. The aminosilane is preferably KH550, and the epoxysilane is preferably KH560.
[0031] The solvent is a mixture of deionized water and anhydrous ethanol. The volume ratio of deionized water to anhydrous ethanol in the solvent is 1:9 to 1:10.
[0032] The total silane mass fraction of the bissilane compound hydrolysate is 1.5%~3%, the hydrolysis pH is 4.5~5.0, and the stirring hydrolysis time is 30~60 min.
[0033] S3. Pretreated wood chips were spray-modified with a bissilane compound hydrolysate, and then aged and dried to obtain bissilane compound modified wood chips.
[0034] In this step, during spray modification, the amount of bissilane compound hydrolysate used is 6% to 10% of the wood chips' mass.
[0035] The aging process was carried out at room temperature for 30 minutes.
[0036] The drying temperature is 105℃ and the drying time is 2~4 hours.
[0037] S4. Mix the polyether polyol and additives evenly to form component A, add the bissilane-modified wood chips and stir to premix, obtaining a uniformly dispersed bissilane-modified wood chip mixture. The additives include amine catalysts and foaming agents.
[0038] In this step, the stirring method is ultrasonic-assisted mechanical stirring; the mechanical stirring speed is 150~200 rpm, the ultrasonic frequency of ultrasonic assistance is 20~40 kHz, and the premixing time is 6~10 min.
[0039] This invention uses ultrasonic-assisted mechanical stirring as a premixing process to achieve uniform dispersion of high-volume wood chips, avoiding the problem of uneven combustion performance caused by wood chip agglomeration and local enrichment in traditional processes.
[0040] The improved mixing method resulted in a wood chip distribution uniformity deviation of ≤3% within the material, with no local overburning or underburning during the deflagration process. The energy output consistency of dry ice blasting was significantly improved, effectively reducing the uncertainty risk of blasting operations.
[0041] The mixed system contains polyether polyol, additives and bissilane-modified wood chips, with the amount of bissilane-modified wood chips added externally ranging from 70% to 90%.
[0042] S5. Add isocyanate to the mixture and stir. Pour into a mold for free foaming and solidify to obtain the finished product.
[0043] In this step, curing is completed at room temperature, and the room temperature curing time is 72 hours.
[0044] Isocyanate is the main component of component B, with an isocyanate index of 1.05~1.10.
[0045] The stirring time for this step is 10-15 seconds.
[0046] The resulting product is the bissilane-modified wood chip polyurethane composite material for dry ice blasting provided by this invention.
[0047] The present invention will be further described in detail below through specific embodiments: Example 1 This embodiment provides a bissilane-modified wood chip polyurethane composite material for dry ice blasting and its preparation method. The preparation method includes the following steps: S1. Wood chip pretreatment: Select wood chips with a particle size of 0.1~3mm, place them in an oven at 105℃ and dry for 3h. Control the moisture content of the dried wood chips to be no more than 0.5% to obtain pretreated wood chips.
[0048] S2. Prepare a bissilane compound hydrolysate by mixing KH550 and KH560 at a mass ratio of 1:1 to obtain a hydrolysate with a total silane mass fraction of 1.5%. The solvent is a mixture of deionized water and anhydrous ethanol, with a volume ratio of deionized water to anhydrous ethanol of 1:9. Adjust the pH of the bissilane compound hydrolysate to 4.5 with glacial acetic acid and hydrolyze at room temperature for 30 minutes until the solution is clear and transparent.
[0049] S3. Spray modification of wood chips: The bissilane compound hydrolysate is atomized and sprayed into the pretreated wood chips at a dosage of 6% of the wood chip mass, while mechanically stirring the wood chips during spraying; the wood chips are uniformly coated with droplets by stirring until the spraying is completed; then aged at room temperature for 30 minutes, and then baked in an oven at 105℃ for 2 hours to obtain bissilane compound modified wood chips.
[0050] S4. Polyol System Composite Premix: Polyether polyol, foaming agent, and amine catalyst are mixed evenly, and then 70% (by weight of the polyurethane foam matrix) of bissilane-modified wood chips are added. The mixture is premixed using ultrasonic-assisted mechanical stirring to obtain a uniformly dispersed bissilane-modified wood chip mixture. The mechanical stirring speed is 150 rpm, the ultrasonic frequency is 20 kHz, and the premixing time is 6 minutes.
[0051] S5. Foaming and Molding: Isocyanate (MDI) is added to the mixing system. The mass ratio of the mixture of polyether polyol, amine catalyst, and foaming agent to isocyanate is 1:1. The isocyanate index is controlled at 1.05. After rapid stirring for 10 seconds, the mixture is poured into a mold and allowed to foam freely at room temperature. After curing for 72 hours, the finished product is obtained. This finished product is a bissilane-modified wood chip polyurethane composite material for dry ice blasting.
[0052] Example 2 This embodiment provides a bissilane-modified wood chip polyurethane composite material for dry ice blasting and its preparation method. The preparation method includes the following steps: S1. Wood chip pretreatment: Select wood chips with a particle size of 0.1~3mm, place them in an oven at 105℃ and dry for 3h. Control the moisture content of the dried wood chips to be no more than 0.5% to obtain pretreated wood chips.
[0053] S2. Prepare a bissilane compound hydrolysate by compounding KH550 and KH560 at a mass ratio of 1:1.02 to obtain a hydrolysate with a total silane mass fraction of 2.0%. The solvent is a mixture of deionized water and anhydrous ethanol, with a volume ratio of deionized water to anhydrous ethanol of 1:10. Adjust the pH of the bissilane compound hydrolysate to 4.8 with glacial acetic acid and hydrolyze at room temperature for 45 minutes until the solution is clear and transparent.
[0054] S3. Spray modification of wood chips: The bissilane compound hydrolysate is atomized and sprayed into the pretreated wood chips at a dosage of 8% of the wood chip mass, while mechanically stirring the wood chips during spraying; the wood chips are uniformly coated with droplets by stirring until the spraying is completed; then aged at room temperature for 30 minutes, and then baked in an oven at 105℃ for 3 hours to obtain bissilane compound modified wood chips.
[0055] S4. Polyol System Composite Premix: Polyether polyol, foaming agent, and amine catalyst are mixed evenly, and then 80% of the mass of bissilane-modified wood chips (by weight of the polyurethane foam matrix) are added. The mixture is premixed using ultrasonic-assisted mechanical stirring to obtain a uniformly dispersed bissilane-modified wood chip mixture. The mechanical stirring speed is 180 rpm, the ultrasonic frequency is 30 kHz, and the premixing time is 8 minutes.
[0056] S5. Foaming and Molding: Isocyanate (MDI) is added to the mixing system. The mass ratio of the mixture of polyether polyol, amine catalyst, and foaming agent to isocyanate is 1:1.05, and the isocyanate index is controlled at 1.08. After rapid stirring for 12 seconds, the mixture is poured into a mold and allowed to foam freely at room temperature. After curing for 72 hours, the finished product is obtained. This finished product is a bissilane-modified wood chip polyurethane composite material for dry ice blasting.
[0057] Example 3 This embodiment provides a bissilane-modified wood chip polyurethane composite material for dry ice blasting and its preparation method. The preparation method includes the following steps: S1. Wood chip pretreatment: Select wood chips with a particle size of 0.1~3mm, place them in an oven at 105℃ and dry for 3h. Control the moisture content of the dried wood chips to be no more than 0.5% to obtain pretreated wood chips.
[0058] S2. Prepare a bissilane compound hydrolysate by mixing KH550 and KH560 at a mass ratio of 1:1.05 to obtain a hydrolysate with a total silane mass fraction of 3%. The solvent is a mixture of deionized water and anhydrous ethanol, with a volume ratio of deionized water to anhydrous ethanol of 1:9. Adjust the pH of the bissilane compound hydrolysate to 5.0 with glacial acetic acid and hydrolyze at room temperature for 60 minutes until the solution is clear and transparent.
[0059] S3. Spray modification of wood chips: The bissilane compound hydrolysate is atomized and sprayed into the pretreated wood chips at a dosage of 10% of the wood chip mass, while mechanically stirring the wood chips during spraying; the wood chips are uniformly coated with droplets by stirring until the spraying is completed; then aged at room temperature for 30 minutes, and then baked in an oven at 105℃ for 4 hours to obtain bissilane compound modified wood chips.
[0060] S4. Polyol System Composite Premix: Polyether polyol, foaming agent, and amine catalyst are mixed evenly, and then 90% of the mass of polyurethane foam matrix is added with bissilane-modified wood chips. The mixture is premixed using ultrasonic-assisted mechanical stirring to obtain a uniformly dispersed bissilane-modified wood chip mixture. The mechanical stirring speed is 200 rpm, the ultrasonic frequency is 40 kHz, and the premixing time is 10 min.
[0061] S5. Foaming and Molding: Isocyanate (MDI) is added to the mixing system. The mass ratio of the mixture of polyether polyol, amine catalyst, and foaming agent to isocyanate is 1:1.1, and the isocyanate index is controlled at 1.10. After rapid stirring for 15 seconds, the mixture is poured into a mold and allowed to foam freely at room temperature. After curing for 72 hours, the finished product is obtained. This finished product is a bissilane-modified wood chip polyurethane composite material for dry ice blasting.
[0062] To verify the technical effects of the present invention, the following comparative examples were also provided: Comparative Example 1 This comparative example provides a wood chip-added polyurethane composite material and its preparation method, wherein the preparation method includes the following steps: S1: Wood chip pretreatment: Select biomass wood chips with a particle size of 0.1~3mm, place them in an oven at 105℃ and dry for 3h, controlling the moisture content to be no more than 0.5%, to obtain pretreated wood chips.
[0063] S2: Polyol system premixing: Polyether polyol, foaming agent, and amine catalyst are mixed evenly, and pretreated wood chips accounting for 80% of the polyurethane foam matrix are added. The mixture is premixed using ultrasonic-assisted mechanical stirring to obtain a uniformly dispersed wood chip mixture. The mechanical stirring speed is 180 rpm, the ultrasonic frequency is 30 kHz, and the premixing time is 8 minutes. The pretreated wood chips are unmodified.
[0064] S3: Foaming molding: Add isocyanate (MDI) to the mixture, control the isocyanate index to 1.08, stir quickly for 12 seconds, pour into the mold, allow it to foam freely at room temperature, and cure for 72 hours to obtain the finished product.
[0065] Comparative Example 2 This comparative example provides a wood chip-added polyurethane composite material and its preparation method, wherein the preparation method includes the following steps: S1: Wood chip pretreatment: Select biomass wood chips with a particle size of 0.1~3mm, place them in an oven at 105℃ and dry for 3h, controlling the moisture content to be no more than 0.5%, to obtain pretreated wood chips; S2: Preparation of monosilane hydrolysate: Prepare a 2% (w / w) KH550 silane hydrolysate using a mixture of deionized water and anhydrous ethanol as the solvent. The volume ratio of deionized water to anhydrous ethanol in the solvent is 1:9. Adjust the pH of the monosilane hydrolysate to 4.8 with glacial acetic acid and hydrolyze at room temperature for 45 minutes until the solution is clear and transparent.
[0066] S3. Spray modification of wood chips: The monosilane hydrolysate is atomized and sprayed into the pretreated wood chips at a dosage of 8% of the wood chip mass, while mechanically stirring the wood chips during spraying; the wood chips are uniformly coated with droplets by stirring until the spraying is completed; then aged at room temperature for 30 minutes, and then baked in an oven at 105℃ for 3 hours to obtain monosilane modified wood chips.
[0067] S4: Polyol System Composite Premix: Polyether polyol, foaming agent, and amine catalyst are mixed evenly, and then 80% of the mass of polyurethane foam matrix is added. The mixture is premixed using ultrasonic-assisted mechanical stirring to obtain a uniformly dispersed mixture of monosilane-modified wood chips. The mechanical stirring speed is 180 rpm, the ultrasonic frequency is 30 kHz, and the premixing time is 8 minutes.
[0068] S5. Foaming and molding: Add isocyanate (MDI) to the mixture, control the isocyanate index to 1.08, stir quickly for 12 seconds, pour into the mold, allow it to foam freely at room temperature, and cure for 72 hours to obtain the finished product.
[0069] Comparative Example 3 This comparative example provides a dual-silane compound modified wood chip polyurethane composite material and its preparation method, which includes the following steps: S1. Wood chip pretreatment: Select wood chips with a particle size of 0.1~3mm, place them in an oven at 105℃ and dry for 3h. Control the moisture content of the dried wood chips to be no more than 0.5% to obtain pretreated wood chips.
[0070] S2. Prepare a bissilane compound hydrolysate by mixing KH550 and KH560 at a mass ratio of 1:1 to obtain a hydrolysate with a total silane mass fraction of 2%. The solvent is a mixture of deionized water and anhydrous ethanol, with a volume ratio of 1:9. Adjust the pH of the bissilane compound hydrolysate to 4.8 with glacial acetic acid and hydrolyze at room temperature for 45 minutes until the solution is clear and transparent.
[0071] S3. Spray modification of wood chips: The bissilane compound hydrolysate is atomized and sprayed into the pretreated wood chips at a dosage of 8% of the wood chip mass, while mechanically stirring the wood chips during spraying; the wood chips are uniformly coated with droplets by stirring until the spraying is completed; then aged at room temperature for 30 minutes, and then baked in an oven at 105℃ for 3 hours to obtain bissilane compound modified wood chips.
[0072] S4. Polyol System Composite Premix: Polyether polyol, foaming agent, and amine catalyst are mixed evenly, and then 80% of the mass of polyurethane foam matrix is added to bissilane-modified wood chips. The mixture is premixed using pure mechanical stirring to obtain a uniformly dispersed bissilane-modified wood chip mixture. The mechanical stirring speed is 180 rpm, and the premixing time is 6 minutes.
[0073] S5. Foaming and Molding: Isocyanate (MDI) is added to the mixture, controlling the isocyanate index to 1.08. After rapid stirring for 12 seconds, the mixture is poured into a mold and allowed to foam freely at room temperature. After curing for 72 hours, the finished product is obtained. This finished product is a bissilane-modified wood chip polyurethane composite material for dry ice blasting.
[0074] The finished products obtained from the above embodiments and comparative examples were used as samples, and untreated loose wood chips were used as the reference group. An explosion test was conducted under the same conditions, and the explosion-related technical indicators were tested. The results are shown in Table 1.
[0075] Table 1. Comparison of technical specifications of the finished products obtained from each embodiment and comparative example.
[0076] The present invention has been described above by way of example with reference to the accompanying drawings. Obviously, the specific implementation of the present invention is not limited to the above-described manner. Any non-substantial improvements made using the inventive concept and technical solution of the present invention, or the direct application of the inventive concept and technical solution of the present invention to other occasions without modification, are all within the protection scope of the present invention.
Claims
1. A bissilane-modified wood chip polyurethane composite material for dry ice blasting, characterized in that, It includes a polyurethane foam matrix and bissilane-modified wood chips, wherein the bissilane-modified wood chips are uniformly dispersed and embedded in the polyurethane foam matrix, and the bissilane-modified wood chips are obtained by modifying wood chips with bissilane.
2. The dual-silane compound modified wood chip polyurethane composite material for dry ice blasting according to claim 1, characterized in that, The amount of bissilane-modified wood chips added is 70-90% of the mass of the polyurethane foam matrix.
3. The bissilane-modified wood chip polyurethane composite material for dry ice blasting according to claim 1, characterized in that, The bissilane compound modification is carried out using a bissilane compound hydrolysate, which includes aminosilane and epoxysilane.
4. The dual-silane compound modified wood chip polyurethane composite material for dry ice blasting according to claim 1, characterized in that, The raw materials of the polyurethane foam matrix include component A and component B. Component A is a mixture of polyether polyol, amine catalyst and foaming agent, and component B includes isocyanate. The mass ratio of component A to component B is 1.0~1.
1.
5. The bissilane-modified wood chip polyurethane composite material for dry ice blasting according to claim 1, characterized in that, The particle size of the bissilane-modified wood chips is 0.1~3mm, and the moisture content of the bissilane-modified wood chips is no more than 0.5%.
6. A method for preparing a bissilane-modified wood chip polyurethane composite material for dry ice blasting according to any one of claims 1-5, characterized in that, Includes the following steps: S1. Screen and dry the sawdust to obtain pretreated sawdust; S2. Prepare a bissilane compound hydrolysate by dissolving aminosilane and epoxysilane in a solvent, adjusting the solvent to acidity, and then stirring to hydrolyze until the solution is clear and transparent. S3. Pretreated wood chips were spray-modified with a bissilane compound hydrolysate, and then aged and dried to obtain bissilane compound modified wood chips. S4. Mix polyether polyol, amine catalyst and foaming agent evenly to form component A, add bissilane compound modified wood chips and stir to premix, to obtain a uniformly dispersed bissilane compound modified wood chips mixture system. S5. Add isocyanate to the mixture and stir. Pour into a mold for free foaming and solidify to obtain the finished product.
7. The method for preparing the bissilane-modified wood chip polyurethane composite material for dry ice blasting according to claim 6, characterized in that, In step S2, the aminosilane is KH550, the epoxysilane is KH560, the solvent is a mixture of deionized water and anhydrous ethanol, the total silane mass fraction of the bissilane compound hydrolysate is 1.5%~3%, the hydrolysis pH is 4.5~5.0, and the stirring hydrolysis time is 30~60 min.
8. The method for preparing the bissilane-modified wood chip polyurethane composite material for dry ice blasting according to claim 6, characterized in that, In step S3, the amount of the bissilane compound hydrolysate used is 6% to 10% of the wood chips' mass.
9. The method for preparing the bissilane-modified wood chip polyurethane composite material for dry ice blasting according to claim 6, characterized in that, In step S4, the stirring method is ultrasonic-assisted mechanical stirring; the mechanical stirring speed is 150~200 rpm, the ultrasonic frequency of ultrasonic assistance is 20~40 kHz, and the premixing time is 6~10 min.
10. The method for preparing the bissilane-modified wood chip polyurethane composite material for dry ice blasting according to claim 6, characterized in that, In step S5, the isocyanate index is 1.05~1.10, and the stirring time is 10~15s.
